THE DEVELOPMENT OF THE ROMAN AND GERMANIC LANGUAGES - Khudoyberdiyeva Durdona Boburovna (TADQIQOTLAR.UZ, 2024)
Abstract. This article discusses the Romance and Germanic languages, which are part of the European language family, and their philological structure. As usual, the history of development was studied.